Trabeculectomy in patients with an advanced stage of glaucoma in Santiago de Cuba - Tania Yelina Silva-Chil; Mabel González-Naranjo; Yargelis González-Orza; Osmani Suárez-Sánchez; Danay Duperet-Carvajal (Revista Información Científica, 2021)
Introduction: behavior in advanced stage glaucoma has brought controversies among specialists in ophthalmology due to its possible visual consequences.